Effect of disabled facility worker’s social support on their job satisfaction - Joo-Yeon Lee; Sung-je Cho (한국정보전자통신기술학회 논문지, 2018)
The purpose of this study is to investigate the difference in social support and job satisfaction of disabled facility workers according to their general characteristics and job characteristics, and to understand the effect of social support on job satisfaction. A questionnaire was conducted against 143 disabled facility workers in D metropolitan city, from 5 January to 29 February 2016. The results of the study are as follows: first, no significant difference was found in the social support of disabled facility workers according to their general characteristics, and only the factor of job area showed significant difference in social support according to job characteristics. Secondly, there was no significant difference in job satisfaction of disabled facility workers according to their general characteristics or job characteristics. Thirdly, support of the superior, as a sub-factor of social support recognised by the disabled facility worker, was found to have a significant positive effect on job satisfaction. This study seeks to become foundational data for the development of plans to improve the job satisfaction of disabled facility workers. KCI Citation Count: 0